Advancing neuromuscular ultrasound through research: Finding common sound. Issue 3 (30th May 2017) - Hobson‐Webb, Lisa D.; Cartwright, Michael S.
ABSTRACT: Introduction: Neuromuscular ultrasound (NMUS) is an accepted, but underutilized, diagnostic tool in the evaluation of neuromuscular disorders. The lack of uniform high‐quality standards in published research and in clinical practice has been a limitation to its growth. Methods: In this article we address the shortcomings of NMUS research and establish basic standards to guide further work in the field. Results: A review of the basic types of NMUS research studies is presented, along with the elements that each should include. Basic standards for this imaging technique are also presented. An explanation of common data elements (CDEs) is provided with discussion of how NMUS may benefit from their creation. Conclusions: High‐quality NMUS research is needed to advance the field. Assuring that publications meet basic standards is essential. In addition, the creation of CDEs specific for NMUS is proposed. Muscle Nerve 56 : 375–378, 2017